Croatian Word Tagging System - SOLAH - Žubrinić, Tomislava; Lauc, Davor; Manucci, Marina (1996)
The system for tagging, lemmatization and analysis of texts written in Croatian language is described.
Projekt MZOS
Projekt MZOS
ENG